Analysis of the transmission mode of sugarcane white leaf phytoplasma in Gengma, Yunnan Province, China. Issue 10 (26th July 2021) - Shan, Hong‐Li; Zhang, Rong‐Yue; Wang, Xiao‐Yan; Cang, Xiao‐Yan; Wang, Chang‐Mi; Li, Wen‐Feng; Yin, Jiong; Luo, Zhi‐Ming; Huang, Ying‐Kun
Abstract: Sugarcane white leaf (SCWL) is a destructive new sugarcane disease that has spread rapidly throughout low‐latitude plateau regions of Yunnan Province, China. To determine the transmission mode of SCWL phytoplasma in this region, the transmission mode of SCWL phytoplasma was analysed in the Gengma sugarcane area of Lincang City, Yunnan Province, where SCWL is severe. Five susceptible sugarcane varieties were grown with phytoplasma‐infected and pathogen‐free seedcane in 2018–2019, and then, systematic comparisons of newly emerging and ratoon crops were carried out. Comparisons using insect‐proof netting were also performed to confirm the role of insect vectors. The average rate of disease in newly emerging and ratoon crops grown with phytoplasma‐infected seedcane was 11.7%–72.9%, while in plants grown with pathogen‐free seedcane, 0% disease was observed. Moreover, the average rate in plants grown with pathogen‐free seedcane under insect‐proof netting was also 0%. These results suggest that the main transmission mode of SCWL phytoplasma was seedcane with phytoplasma in Gengma sugarcane area (SCWL serious occurrence area) of Lincang City, Yunnan Province. These findings provide a foundation for further studies of sugarcane phytoplasma disease, as well as a scientific basis for the effective prevention and control of SCWL in low‐latitude plateau regions in Yunnan Province.